E-commerce: A platform for local economic development? Evidence from Taobao Villages in Zhejiang Province, China. Issue 3 (September 2022) - Phelps, Nicholas; Wang, Cassandra; Miao, Julie T; Zhang, Jia
In contrast to the one village one product (OVOP) and joint action (JA) models, e-commerce disintermediation is the focus of the Taobao village (TV) model pioneered in China. Drawing on original questionnaire survey data of village heads' perceptions of the adoption of the TV model in 300 Taobao villages in Zhejiang province, we investigate: (1) the significance of the TV phenomenon; (2) the perceived benefits and disbenefits of the adoption of the Taobao business model on villages; (3) and the institutionalisation of the TV model. While the TV model remains weakly institutionalised, its effects appear to exceed those of the OVOP and JA models when raising rural employment and incomes but also appearing to promote selected dynamic economic gains and elements of diversification of livelihoods.